2021
DOI: 10.5194/gi-2021-16
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating methods for reconstructing large gaps in historic snow depth time series

Abstract: Abstract. Historic measurements are often temporally incomplete and may contain longer periods of missing data whereas climatological analyses require continuous measurement records. This is also valid for historic manual snow depth (HS) measurement time series, where even whole winters can be missing in a station record and suitable methods have to be found to reconstruct the missing data. Daily in-situ HS data from 126 nivo-meteorological stations in Switzerland in an altitudinal range of 230 to 2536 m above… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In this way, stations that were unsuitable for filling gaps could be easily identified and excluded from the calculations. A recently performed comparison of gap‐filling methods for snow depth time series (Aschauer and Marty, 2021) showed that there are better methods than GIDS available, less impacted by station density. However, with carefully performed plausibility checks the method produced useful results.…”
Section: Methodsmentioning
confidence: 99%
“…In this way, stations that were unsuitable for filling gaps could be easily identified and excluded from the calculations. A recently performed comparison of gap‐filling methods for snow depth time series (Aschauer and Marty, 2021) showed that there are better methods than GIDS available, less impacted by station density. However, with carefully performed plausibility checks the method produced useful results.…”
Section: Methodsmentioning
confidence: 99%